2008
DOI: 10.1007/s12010-008-8322-0
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Methionine Enhanced the Ergothioneine Accumulation in the Ganoderma neo-japonicum Mycelia

Abstract: The methods for increasing the production of ergothioneine (ERG) were investigated by using the mycelial culture of several mushroom species, primarily Ganoderma neo-japonicum. We first found that ERG was accumulated at the different levels in mycelia and fruiting bodies, respectively, depending on the mushroom species. As a result of adding various amino acids to the mycelial culture medium, methionine (Met) was shown to be the most effective additive. The most preferable condition of the additive was the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…Previously, we have shown that the supplementation of Met in culture media increased the ERG production in the Ganoderma neo-japonicum mycelia (Lee et al, In press). It has long been known that ERG is synthesized from the amino acids, such as histidine (His), Met, and Cysteine (Cys) (Askari and Melville, 1962).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously, we have shown that the supplementation of Met in culture media increased the ERG production in the Ganoderma neo-japonicum mycelia (Lee et al, In press). It has long been known that ERG is synthesized from the amino acids, such as histidine (His), Met, and Cysteine (Cys) (Askari and Melville, 1962).…”
Section: Resultsmentioning
confidence: 95%
“…It has long been known that ERG is synthesized from the amino acids, such as histidine (His), Met, and Cysteine (Cys) (Askari and Melville, 1962). Cys and Met increased the ERG levels up to 1.7- and 3.1-fold, respectively, although His did not (Lee et al, In press). In order to know if the Met supplementation also increases the ERG levels in other mushroom species, two mmol of Met was added to the mycelial culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…All needle samples were prepared in a 5% PCA solution for further analysis. The amino acid content was analyzed as previously described (Lee et al, 2009) using a HPLC system (Thermo Electron Co, Finnigan Surveyor System, MA, USA) equipped with a Waters Pico-Tag column (3.9 mm × 150 mm, 5 m; Waters, MA, USA) and UV detector. The same HPLC was used for all other measurements described below.…”
Section: Metabolic Analysesmentioning
confidence: 99%
“…Several studies involving the manipulation of culture media constituents have been conducted to improve the accumulation of ESH in fruiting bodies and mycelia (Dubost et al 2007;Estrada et al 2009;Lee et al 2009). However, the relationship between the morphology of mycelia and ESH production, which might assist in designing the physicochemical parameters of a liquid fermentation system to facilitate the enriched production of ESH, has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%